Sibutramine antinociceptive effect in female rodents is not dependent on catecholaminergic signaling - Sales,Maria; Figueiredo,Karolinne S; Fontenele,Juvenia B; Viana,Glauce SB; Felix,Francisco HC (PeerJ PrePrints, 2015)
​Sibutramine has a mechanism of action similar to that of antidepressants used as analgesics (like duloxetine). Limited data exists regarding the analgesic action of sibutramine. We tested increasing doses of p.o. sibutramine (0.1, 0.5, 1.5, 5.0 mg/kg) in the writhing test in female mice and in the plantar thermal hyperalgesia induced by carrageenan in female rats. The results showed a statistically significant (p<0.001) dose-response antinociceptive effect of sibutramine in these models, with a maximum effect comparable to the effect of a high dose of ASA (200 mg/kg) in mice and amitriptyline (10mg/kg) or indomethacin (10mg/kg) in rats. Rotarod test with sibutramine-treated rats ruled out motor impairment. Sibutramine-induced antinociception was not reverted by reserpine or yohimbine pre-treatment, suggesting that catecholamines and alpha-2-adrenoceptors are not involved in this effect.
Keywords: sibutramine; analgesia; thermal hyperalgesia; catecholamines; chronic pain